Unraveling the Complex Features of the Seismic Scatterers in the Mid‐Lower Mantle Through Phase Transition of (Al, H)‐Bearing Stishovite - Yingxin Yu; Youyue Zhang; Luo Li; Xinyue Zhang; Denglei Wang; Zhu Mao; Ningyu Sun; Yanyao Zhang; Xinyang Li; Wancai Li; Sergio Speziale; Dongzhou Zhang; et al. (Geophysical Research Letters, 2025)
Abstract Small‐scale scatterers observed in the mid‐lower mantle beneath the subduction zones are thought to result from the phase transition of stishovite within subducted oceanic crusts. Here we investigate the phase transition of (Al, H)‐bearing stishovite with four compositions at simultaneously high P‐T conditions combining Raman spectroscopy and X‐ray diffraction. These experimental results reveal that the incorporation of 0.01 a.p.f.u Al into stishovite with H/Al ratio of ∼1/3 lowers the transition pressure by 6.7(3) GPa. However, the Clapeyron slope of this transition is nearly unaffected by changes in the Al content and has a value of 12.2–12.5(3) MPa/K. According to our results, Al content variation ranging from 0 to 0.07 a.p.f.u in SiO2 can reasonably explain the depth distribution from 800 to 1,900 km of the seismic scatterers observed in the circum‐Pacific region. These results deepen our understanding on the complex features of mid‐lower mantle seismic scatterers and corresponding dynamic processes.